Humans as Subjects and Objects of Education: Reflection from Surah At-Tin Verses 4-6 - Yuniartin, Titin; Aprilia, Donna; Nihayatus Sholihah, Nita (CV. Kalimasada Group, 2025)
This study aims to examine the role of humans as subjects and objects in education based on the reflection of Surah At-Tin verses 4-6. This Surah portrays humans as beings created in the best form (ahsani taqwim) with the potential to fall to the lowest state (asfala safilin) if they fail to maintain faith and righteous deeds. The research method used is library research with a descriptive-qualitative approach, analyzing the meaning of the verses from the Qur'an and linking them to Islamic education theory. The results of the study show that as subjects of education, humans are responsible for developing themselves through the pursuit of knowledge, while as objects, humans require guidance to achieve their full potential. Islamic education, based on Qur'anic values, plays a vital role in maintaining the balance between physical and spiritual dimensions, as well as in shaping the moral and spiritual character of individuals. In conclusion, education based on religious values and the Qur'an plays a strategic role in guiding humans to fulfill their roles as active subjects and as objects requiring guidance to achieve the ultimate goal of life as khalifah on earth.